2010
DOI: 10.1002/acr.20321
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgA rheumatoid factor and pyridinoline in very early arthritis as predictors of erosion(s) at two years: A simple model of prediction from a conservatively treated community‐based inception cohort

Abstract: Objective. To identify, in conservatively treated, very early arthritis patients, predictors of >1 erosion(s) at 2 years, and to construct a prediction model. Methods. Community-based adults (n ‫؍‬ 310) who had never taken disease-modifying antirheumatic drugs (DMARDs) or steroids with swelling of >2 joints persisting for >4 weeks and lasting <6 months were recruited. Erosion status was assessed at 0, 6, 12, and 24 months; evaluations were comprised of clinical criteria (Disease Activity Score, Health Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In fact, Loët et al (2010) showed that IgA-Rheumatoid factors and pyridinoline, were risk factors for erosions when their levels were simultaneously elevated [22]. The same results were reported by Krabben et al (2013) which found that increased pyridinoline serum levels, both at baseline and during the disease course, were associated with more severe joint damage during the following year s [23].…”
Section: Discussionmentioning
confidence: 64%
“…In fact, Loët et al (2010) showed that IgA-Rheumatoid factors and pyridinoline, were risk factors for erosions when their levels were simultaneously elevated [22]. The same results were reported by Krabben et al (2013) which found that increased pyridinoline serum levels, both at baseline and during the disease course, were associated with more severe joint damage during the following year s [23].…”
Section: Discussionmentioning
confidence: 64%
“…It comprised 310 patients: male or female, age ≥ 18 years; ≥ 2 swollen joints, swelling persisting for > 4 weeks, symptoms lasting < 6 months; no previous glucocorticoid prescription [only one intra-articular injection > 1 month before or oral prednisone (<10 mg/day) for 1 week > 2 weeks before enrollment were tolerated] or disease-modifying antirheumatic drugs (DMARDs); no inflammatory back pain; no foreseen move during the 10 next years. The protocol recommended conservative treatment within the first two years [8]. This study was approved by the Upper Normandy Ethics Committee (file 95/138/HP).…”
Section: Methodsmentioning
confidence: 99%
“…The VErA cohort was described previously [8]. Briefly, this community-based, inception cohort was recruited between 1998 and 2002 in two French regions.…”
Section: Methodsmentioning
confidence: 99%
“…Serum IgA anti-gluten and anti-transglutaminase antibodies are observed in celiac disease, and serum IgA levels can be elevated in inflammatory bowel disease (7,8). IgA pemphigus appears to be driven by direct autoreactivity, and the circulating level of IgA rheumatoid factor has a high prognostic value in rheumatoid arthritis (9,10). In so-called seronegative lupus nephritis, a "full house" nephropathy pattern can be frequently observed that includes IgA deposition in the glomeruli (11).…”
Section: Introductionmentioning
confidence: 99%